CLOUD ACCOUNTING IMPACT ON FINANCIAL REPORTING QUALITY IN SMES: REVIEW ARTICLE - Yousif Ibrahim Najmaldin; Wan Sallha Yusoff; Zardasht Abubaker Qader Barzinji, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This review examines the literature using mixed methods to assess current information and knowledge gaps related to cloud accounting processes in SMEs. Therefore, from this point of view, cloud accounting is crucial for businesses because companies provide information to multiple parties and therefore require reliable and protected financial reporting. Therefore, this article provides a comparative discussion by examining and evaluating the perspectives of researchers and practitioners in the field of cloud accounting. Through the research, the weaknesses of cloud accounting in the operations of small and medium enterprises are revealed. The lack of physical openness to globalization and technology, immersion in this deep world, and following traditional methods, which has led to not keeping pace with the modern era and the economic climate, are all factors that prevent financial institutions from keeping pace with progress. Therefore, the recommendation of this study is for researchers to avoid the mistakes of the past in relying on traditional methods. More importantly, the assumption of a clear link between two variables is evidence of these flaws. This basic area of research would contribute significantly to adopting a more thoughtful framework for finding causal relationships.